From Theory to Engagement : Reconceptualizing Public Relations in the Digital Communication Era - Luhukay, Marsefio (Journal of Content and Engagement, 2026)
The digital revolution has fundamentally altered the conditions under which Public Relations (PR) is practiced, yet the field's foundational theoretical frameworks, developed largely in an era of mass media and linear communication flows, have not been systematically reconceptualized to account for the communicative realities of the platform era. This article addresses that gap through an integrative review methodology and conceptual analysis, re-examining four classical PR theories: Grunig and Hunt's two-way symmetrical communication model, Cutlip, Center, and Broom's relationship management theory, the framing and agenda-setting framework, and Rogers's diffusion of innovation theory. Each is reinterpreted through the lens of contemporary digital phenomena including social media algorithms, artificial intelligence, cancel culture, and ESG accountability demands. Two globally recognized case studies are integrated as illustrative anchors: Stanley's viral TikTok crisis response (2023-2024), which illustrates real-time two-way engagement at scale, and Unilever's sustained ESG communication strategy (2022-2024), which demonstrates how relationship management has evolved into a purpose-driven stakeholder engagement model. The article's original contribution is the Integrated Engagement Model, a unified conceptual framework that reconceptualizes PR's four classical theoretical pillars simultaneously and coherently in response to digital, AI, and ESG imperatives. Unlike existing studies that address these transformations in isolation, this article provides a synthesized reconceptualization across all four theoretical dimensions, proposing that PR must transition from message management to engagement architecture as the governing paradigm for contemporary practice.